TURKEY’S STRATEGY TOWARDS AFGHANISTAN: SECURITY AND DEVELOPMENT ASSISTANCE - A. I. Aliyeva (Vestnik MGIMO-Universiteta)
Providing assistance to the least developed countries has remained one of the top priorities for leading international actors in the XXI century, and the Republic of Turkey is no exception in this regard. The Justice and Development Party's ascension to power in 2002 led to a drastic revision of the Turkish foreign policy and adoption of a novel approach to the least developed countries accounting for the complex interdependence between security and development. This approach was tested in Afghanistan where Turkey contributed to both post-conflict reconstruction of the country and to the activities of the International Security Assistance Force (ISAF). Since 2015 Turkey has been actively engaged in the new NATO 'Resolute Support' mission, while continuing its economic support to Afghanistan on bilateral and multilateral basis. This paper aims to unveil the particularities of the Turkey's Afghan strategy, which has yet escaped the Russian scholars' attention, with the help of the Turkish primary sources and academic works. It studies the specificity of bilateral relations and their determinants, including historic ties and religious and cultural proximity. It provides an in-depth analysis of the activities of both Turkish Cooperation and Development Agency (TIKA) and the Turkish Provincial Reconstruction Team (PRT) in Afghanistan and examines the challenges of Turkish troops' presence on the Afghan soil and the way how the Turkish elites and Turkey's NATO allies perceive it.